(3YeQ Hf bOhQ GdLRGFQj (B:s (3QGFO GdUMGaI GdEUdGMjI aj GdLRGFQ(B1906-1927(3OQGSI JMdjdjI (B/s - (3SGMd, YHO GdMejOs ((3GdLRGFQ (B:s (3GdeDSSI GdhWfjI ddfTQ h GdETgGQ ,s, 2016)
(3YeQ Hf bOhQ GMO QehR GdUMGaI GdYQHjI GdLRGFQjI hQGFOgG agh ef GdGbWGH GdChGFd GdPjf SGgehG HLgOge aj GdJYQja HGdbVjI GdLRGFQjI ef NdGd cJGHGJg GdeNJdaI aj GdLQGFO GdYQHjI ceG cGf QGFOG ef QhGO GdGUdGM HGdLRGFQ QZe XQha GdGMJdGd GdaQfSj hLQGFeg gPG GdcJGH JCcjO MbjbI JGQjNjI hacQjI aj Cf hGMO , hgj JHdhQ GdeeGQSI GdEUdGMjI hGdJfhjQjI HTcd hGVM ef NdGd GdGfJGL GdUMaj ddeacQ hGdUMaj YeQ Hf bOhQ GdLRGFQj , hgPG efP GdHOGjGJ GdGhdi ddbQf GdYTQjf , Ch HGdJMOjO HXghQ Chdi cJGHGJg GdUMGajI aj GdLRGFQ HOGjI ef SfI (B1906 (3YHQ UMjaI (B" (3GdgdGd (B"s
Keywords: (3GdUMGaIs; (3YeQ Hf bOhQ GdLRGFQjs